Undergraduate Gender and Its Pedagogical Implications in Oral Performance Education: جنس الطلاب الجامعيين وآثاره التربوية في تعليم الأداء الشفهي - Muhammad Ivan Alfian; Muhammad Zakki Masykur; Sugeng Ali Mansur (Journal of Arabic Language Teaching, 2021)
Psychological factors, including gender differences, strongly influence students' success in mastering speaking skills. This study aims to describe: (1) the relationship of gender with oral language performance in students of the Arabic Education Studies program at the Islamic Institute of the Holy Country and (2) the implications of gender differences in Arabic language learning. This study uses quantitative methods with a sample of 66 of the 108 students in the second semester of the Arabic education study program at the Islamic Institute of the Holy Land, and the data collection method is a test. With linear regression analysis and bivariate correlation analysis, Pearson. The results showed that: (1) there is a gender relationship with oral language performance, where the Pearson correlation value of 0.257 or the value of R count is greater than the value of the R table, as well as the influence of gender on oral language performance by 6.6% (2) The selection of appropriate learning strategies by students will be able to overcome individual differences or gender, where the results of this study indicate that female student are better than men in Arabic speaking skills. إن عوامل الطلاب النفسية لها أثر كبير في نجاح الطلاب عند تعلم مهارة الكلام، ومن العوامل النفسية هي الفروق بين الجنسين. فيهدف هذا البحث إلى وصف: (1) علاقة الجنس بالأداء الشفهي لدى طلاب قسم تعليم اللغة العربية في الجامعة الإسلامية الحكومية بقدس، (2) الاستفادة من الفروق بين الجنسين في تعليم اللغة العربية. استخدم البحث الكمي مع عينة البحث هي 66 طالبا من 108 طالب في قسم تعليم اللغة العربية للمرحلة الثانية في الجامعة الإسلامية الحكومية بقدس وأساليب جمع البيانات هي الاختبار. مع تحليل الانحدار الخطي وتحليل الارتباط الثنائي المتغير بيرسون.دلت نتائج البحث إلى: (1) وجود علاقة بين الجنس والأداء الشفهي، حيث نتيجة Pearson Correlation 0،257 أو r الحسابي أكبر من 0،244(r الجدولي). والجنس يؤثر 6،6 % على التحصيل الدراسي في الأداء الشفهي. (2) أن اختيار استراتيجيات التعلم المناسبة من الطلاب يستطيع أن يتغلب على الفروق بين الجنسين حيث يدل هذا البحث إلى تفوق الإناث على الذكور في الأداء الشفهي أو الكلام.